Synthesis and Characterization of Zinc(II) and Cadmium(II) Complexes of with Piperidinomethylmaleic Hydrazide - Santhi, P.R.; Poongothai, G. (Asian Journal of Chemistry, 2010)
In the present study, zinc(II) and cadmium(II) complexes of Mannich base piperdinomethylmaleic hydrazide (PMMH) were synthesized.